Strategy to Increase Local Economic Competitiveness Through Local Wisdom-Based Creative Economy - Thalib, Bahrun; Prihanto, Purwaka Hari; Mu'ah, Mu'ah (PT. Anagata Sembagi Education, 2024)
The competitiveness of the local economy is crucial for fostering sustainable growth, especially in the face of increasing global competition. One effective strategy to enhance competitiveness is through the development of a creative economy based on local wisdom. However, integrating local values into creative economy development strategies remains a significant challenge. This study aims to analyze the influence of Local Economic Competitiveness on the Creative Economy, with Local Wisdom serving as a mediating variable. A quantitative approach was adopted, using a survey method involving 110 purposively selected respondents, who are creative economy actors based on local wisdom, with at least two years of experience and from regions with notable local wisdom potential. Data were collected using a Likert scale-based questionnaire to measure Local Economic Competitiveness, Local Wisdom, and the Creative Economy. The analysis was performed using SmartPLS software, testing the outer model to assess instrument validity and reliability, and the inner model to evaluate relationships between latent variables. The results indicate that Local Economic Competitiveness positively and significantly affects the Creative Economy, both directly and indirectly through Local Wisdom. Local Wisdom plays a crucial role in strengthening the connection between local economic competitiveness and creative economy development. The findings suggest that strategies to improve local economic competitiveness should leverage local wisdom to foster innovative and sustainable creative economic growth, offering valuable insights for policymakers and practitioners in integrating local values into creative economy development.